Longevity pathways and memory aging - Gkikas, Ilias; Petratou, Dionysia; Tavernarakis, Nektarios (Frontiers in Genetics, 2014)
The ageing process has been associated with numerous pathologies at the cellular, tissue, and organ level. Decline or loss of brain functions, including learning and memory, is one of the most devastating and feared aspects of ageing. Learning and memory are fundamental processes by which animals adjust to environmental changes, evaluate various sensory signals based on context and experience, and make decisions to generate adaptive behaviours. Age-related memory impairment is an important phenotype of brain ageing. Understanding the molecular mechanisms underlying age-related memory impairment is crucial for the development of therapeutic strategies that may eventually lead to the development of drugs to combat memory loss. Studies in invertebrate animal models have taught us much about the physiology of ageing and its effects on learning and memory. In this review we survey recent progress relevant to conserved molecular pathways implicated in both ageing and memory formation and consolidation.